Analyze the Guidelines for Writing Research Approach on Graphic Design Methods using Visual Illusion Art - Hu, Jiawei; Puntien, Pisit (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: Visual illusion art offers unique, innovative value in graphic design, enabling designers to break conventional thinking patterns and enhance the expressiveness and appeal of their work. However, there is a lack of systematic and practical guidance for applying visual illusion techniques in design. To address this gap, this study systematically summarizes the application methods of visual illusion in graphic design, culminating in the book Research on Graphic Design Methods Based on Visual Illusion Art. Unlike existing studies focused on theoretical discussions, this book integrates theoretical foundations with methodological frameworks and practical applications, aiming to help designers master visual illusion principles and enhance the innovation, expressiveness, and visual impact of their work. Materials and Methods: A mixed-methods approach was adopted, combining qualitative methods (literature review, field investigation, case studies, and interviews) with quantitative analysis (surveys and statistical evaluation of the book’s effectiveness). This approach ensures both theoretical depth and practical relevance in exploring the application of visual illusion in graphic design. Results: Key findings include: (1) Visual illusion-based design methods are classified into five categories: geometric, color, motion, spatial, and multi-meaning figure illusions. (2) Visual illusion art helps designers overcome traditional design limitations, fostering creativity and expressive potential. (3) The book provides designers and students with structured methodologies and creative inspiration, improving their design skills, originality, and visual appeal. Conclusion: This study enriches design methodologies by proposing a classification system and application methods for visual illusion, offering designers systematic tools to expand their creative thinking and enhance the expressiveness of their work. Additionally, the study contributes to design education by providing new teaching resources that help students gain a deeper understanding of visual illusion techniques, thereby improving their practical and innovative capabilities.